International liquidity shocks and the European sovereign debt crisis: Was euro area unconventional monetary policy successful? - Mary M. Everett (FIW - Research Centre International Economics, 2015)
Using novel data on individual euro area banks' balance sheets this paper shows that exposure to stressed European sovereigns manifested in a liquidity shock to their international funding through two channels: (i) a contraction in cross-border funding, and (ii) a contraction in US wholesale funding. The effectiveness of the ECB's unconventional monetary policy measures, in the form of the 3-year Long-Term Refinancing Operations (VLTROs), in mitigating effects of the European sovereign debt crisis on the supply of private sector credit is assessed. Controlling for banks' risk factors and credit demand, the first round of VLTROs in December 2011 is not found to have been successful in offsetting the decline in credit supply to Households and non-financial corporates. In contrast, the VLTROs in February 2012 are found to have mitigated the effect of the European sovereign debt crisis on credit supply. Moreover, a contraction in credit supply to non-financial corporates, but not households, is documented for euro area banks affected by the international liquidity shock and that drew on ECB liquidity under the VLTRO facilities.
Keywords: F60; G21; G15; H63; 330; European sovereign crisis; cross-border banking; sovereign debt; international transmission; non-standard measures; ECB liquidity